High-Resolution Profiling of Innate Immune Responses by Porcine Dendritic Cell Subsets in vitro and in vivo - Auray, Gaël; Talker, Stephanie C.; Keller, Irene; Python, Sylvie; Gerber, Markus; Liniger, Matthias; Ganges, Llilianne; Bruggmann, Rémy; Ruggli, Nicolas; Summerfield, Artur (Frontiers in Immunology, 2020)
The present study investigated the transcriptomic response of porcine dendritic cells (DC) to innate stimulation in vitro and in vivo. The aim was to identify DC subset-specialization, suitable toll like receptor (TLR) ligands targeting plasmacytoid DC (pDC), and the DC activation profile during high and low virulent classical swine fever virus (CSFV) infection, chosen as model for a virus causing a severe immunopathology. After identification of porcine conventional DC (cDC) 1, cDC2, pDC and a monocyte-derived subset in lymphoid tissue, we characterized DC activation using transcriptomics, and focused on chemokines, interferons, cytokines, as well as on co-stimulatory and inhibitory molecules. We demonstrate that porcine pDC provide important signals for Th1 and interferon responses, with CpG triggering the strongest responses in pDC. DC isolated from infected pigs early after infection showed prominent upregulation of CCL5, CXCL9, CXCL10, CXCL11 and XCL1, as well as of the cytokines TNFSF13B, IL6, IL7, IL12B, IL15, IL27. IL12B and many interferon genes were mostly restricted to pDC. Interestingly, the infection was associated with a prominent induction of inhibitory and cell death receptors. When comparing low and high virulent CSFV strains, the latter induced a stronger inflammatory and antiviral response but a lower cell cycle response and reduced antigen presentation functions of DC. Taken together, we provide high-resolution information on DC activation in pigs, as well as information on how DC modulation could be linked to CSFV immunopathology.